Detection of Gene E6 HPV 18 With Real Time PCR (Polymerase Chain Reaction) Using Isolated Samples of Uterine Cancer Patients in Riau Province - Hari, Dewi Gulyla (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2021)
One indication that there has been malignancy in cervical lesions due to exposure to high-risk hpv types such as HPV 16 and 18 is the detection of oncogene DNA in the cervical tissue of cancer patients. The oncogenes are the E6 and E7 genes. Previous research data showed evidence that the prognosis of HPV 18 is more massive than that of other high-risk HPV types such as HPV 16. Thus, the effort to detect the E6 gene from biopsy samples of patients suspected of cervical cancer is the right and effective step in order to establish an accurate diagnosis of cervical cancer itself, especially caused by HPV 18.